Pathway to Justice? The Role of Racial Bias Training in Modern Canadian Policing - Samuels-Wortley, Kanika (Canadian journal of criminology and criminal justice, 2025)
Despite the widespread implementation of anti-bias training programs tailored to policing, Canadian academic literature offers few studies examining officers’ attitudes towards and perceptions of these programs and their influence over time. This study addresses this gap by evaluating an anti-racism training module focused on the impact of racial trauma and the historical and ongoing effects of race and racism in Canadian policing. The training, mandated for newly recruited frontline officers in a Canadian municipal police agency, was assessed using a longitudinal, multi-method design, including one-on-one semi-structured interviews, conducted with the newly recruited officers 12-18 months after going into the field. Findings indicate that while officers initially engaged in critical self-reflection, citing concrete ways officers may foster more positive interactions with black and racialized communities, such reflections diminished over time. After one year in the field, officers de-emphasized the relevance of racial trauma training, citing operational priorities, race-neutral approaches to citizen engagement, and references to generational and recruitment-based progress in policing. This study discusses implications for the design of future training initiatives and broader institutional reforms aimed at addressing racial bias in law enforcement.